PERAMPASAN ASET HASIL TINDAK PIDANA KORUPSI TANPA PEMIDANAAN (NON-CONVICTION BASED ASSET FORFEITURE) BERDASARKAN HUKUM INDONESIA DAN UNITED NATIONS CONVENTION AGAINST CORRUPTION (UNCAC) - Abdullah, Fathin; Eddy, Prof. Triono; Marlina, Dr (Jurnal Ilmiah Advokasi, 2021)
Asset forfeiture is a solution to the problem asset forfeiture when a person cannot be criminally prosecuted on the grounds of death or cannot follow the criminal prosecution process as referred to in Article 77 and Article 83 of the Criminal Code of Indonesia. NCB Asset Forfeiture wants the seizure of assets resulting from corruption crimes without having to wait for a criminal verdict and is an alternative if a corruptor can’t criminally prosecuted. The regulation of asset seizure resulting from corruption by mechanism without criminalization in Indonesian law is stipulated in Article 32, Article 33, Article 34, and Article 38C of the Law of the Republic of Indonesia Number 20 of 2001 concerning Amendments to Law No. 31 of 1999 concerning the Eradication of Corruption Crimes while the arrangement of asset forfeiture resulting from corruption crimes by mechanism without criminalization to UNCAC is stipulated in Article 54 chapter (1) letter c UNCAC. The application of NCB Asset Forfeiture in Indonesia in addition to being implemented based on the Law on the Eradication of Corruption Crimes, the State Attorney must be able to prove there has been a real loss of state finances, financial losses of the country due to corruption crimes and there are guarantees from corruptors to facilitate the application of asset seizures resulting from corruption without criminalization. Keywords: Asset Forfeiture, Proceeds of Corruption, Without Criminalization, United Nations Convention Against Corruption.